Perceived Stress and Anxiety Levels of Teachers Toward an Intervention Program - Dominado, Noel L.; Atienza, Yves Ivan Manabat (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
This study evaluated teachers' perceived stress and anxiety levels. This study put into open and addressed the gap among the perceived stress and anxiety levels of the participants of the study as an input to an intervention program for the 39 teaching personnel of one of the leading university extension campuses in the province of Pampanga for the academic year 2021-2022. The study has 2 phases: the quantitative and the qualitative phase. This study was assessed through a 5-point type-Likert questionnaire, which is the Perceived Stress Scale (PSS) (1983) PROMIS Health Organization (PHO), and PROMIS Cooperative (2012). The Sequential Explanatory Approach was used in this study. In the quantitative data analysis of the results, the mean, frequency, standard deviation, and Pearson correlation were used. Outliers were then identified and used as variables in the qualitative process. For the qualitative part, interview transcriptions were included, and transcribed data were extracted and labeled to units of meaning through key point coding. Codings with similarities were grouped into concepts that were analyzed to form themes. There were 10 teachers as participants to collect qualitative data, an open-ended interview was used. Findings revealed that the participants’ perceived stress contributed to low self-esteem and life irritations. Also, it revealed that participants encountered worry, nervousness, and tension; all of these symptoms brought about by anxiety. This study also revealed that there is no relationship between the demographic profiles of the respondents and their perception of stress and anxiety. Due to the positive result of the research, and the lack of stress and anxiety management programs in the institution, this study recommended a program that was formulated and then validated by the expert to provide reasonable practices and approaches to the stress and anxiety of the participants.